TRAILER: SCREEN COMMERCIAL OR MINIFILM? / ТРЕЙЛЕР: ЭКРАННАЯ РЕКЛАМА ИЛИ МИНИФИЛЬМ? - Glazova M.S. / ГЛАЗОВА М.С.; Savelyeva O.O. / САВЕЛЬЕВА О.О. (Наука телевидения)
The authors examine the functions and construction of the trailer in the movie. The competition for viewers is growing, and the viewer needs guidance to select the most interesting and useful. The idea of the film before the preview is formed by advertising campaign where the most effective and informative means of promotion of the film is the trailer. It is a video consisting of the most spectacular film frames mounted in a single composition.